2015
DOI: 10.1590/0001-3765201520140155
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of the Brazilian Air Transportation Network

Abstract: The air transportation network in a country has a great impact on the local, national and global economy.In this paper, we analyze the air transportation network in Brazil with complex network features to better understand its characteristics. In our analysis, we built networks composed either by national or by international flights. We also consider the network when both types of flights are put together. Interesting conclusions emerge from our analysis. For instance, Viracopos Airport (Campinas City) is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 13 publications
0
17
0
10
Order By: Relevance
“…Trata-se de um subconjunto do sistema completo, o qual inclui passageiros e carga e é formado por cerca de 850 aeroportos. Por outro lado, quando comparada com outras redes de transporte de carga e passageiros no mundo, como a do Brasil que é formada por 120 aeroportos (Couto et al, 2015), a rede GT20 mostra-se consideravelmente superior. A Figura 1 apresenta a quantidade de aeroportos para cada rede específica.…”
Section: Análise E Resultadosunclassified
See 2 more Smart Citations
“…Trata-se de um subconjunto do sistema completo, o qual inclui passageiros e carga e é formado por cerca de 850 aeroportos. Por outro lado, quando comparada com outras redes de transporte de carga e passageiros no mundo, como a do Brasil que é formada por 120 aeroportos (Couto et al, 2015), a rede GT20 mostra-se consideravelmente superior. A Figura 1 apresenta a quantidade de aeroportos para cada rede específica.…”
Section: Análise E Resultadosunclassified
“…A seguir são apresentados os conceitos relacionados ao conjunto de métricas de rede utilizadas no presente estudo, com base em Newman (2003), Reka e Barabási (2002) e Couto et al (2015).…”
Section: Métricas De Redeunclassified
See 1 more Smart Citation
“…In spite of this, scalefreeness has been claimed for the Italian [11] (42 airports), Indian [12] (79 airports), the Brazilian [13] (120 airports), or the Chinese network [14] (128 airports). The situation is even worse in the case of road networks, in which the physical nature of the graph implies that the degree of each node is limited, as, for instance, it is difficult to plan a crossroad where more than six streets converge.…”
Section: Common Pitfalls and Misleadingmentioning
confidence: 99%
“…Cardillo et al (2013) [9] used real data from the European Air Transport Composite Network to analyze the structural characteristics of an essentially multilayer real network. Couto et al (2015) [10] analyzed the complex network characteristics of the Brazilian air transport network and confirmed that the network had small-world characteristics, while the national connection network followed a power law distribution. Sun et al (2016) [11] found that most of Dublin's important nodes and transportation hubs were located in the city center, i.e., most bus lines often intersect with the city center.…”
mentioning
confidence: 99%